Prinsip Keadilan dan Musyawarah dalam Hukum Islam Serta Implementasinya dalam Negara Hukum Indonesia - Hariyanto Hariyanto (UIN Sunan Kalijaga Yogyakarta, 2015)
Social equity and the principle of musyawarah within the law state of Indonesian is a fundamental principle. This article proves that, according to Islamic law, justice can be seen from two aspects, legal justice and social justice. Legal justice is closely related to the implementation of the law, while social justice different from the concept of social justice socialist-communist or liberal groups. The concept of social justice based on the notion of social welfare, while principle of musyawarah is based on the family spirit.